Sub-District Head Leadership in Batabual Sub-District, Buru Regency - Rina Buton; Aminah Bahasoan; Ivonny Yeany Rahanra (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This research is a qualitative study with a sample size of 9 participants. It aims to examine the leadership of the Sub-District Head in Batabual Sub-District, Buru Regency. The study was conducted at the Batabual Sub-District Office in Buru Regency. Primary data collection was carried out through interviews with several informants directly involved in the leadership process of the Sub-District Head in Batabual. The findings of this study indicate that the leadership of the Sub-District Head in Batabual Sub-District cannot yet be considered effective and does not meet the standards expected by employees and the community. Consequently, aspects such as service delivery, community empowerment, and infrastructure remain inadequate.